CHARACTERISTICS OF CRITERIA - Ronald Suter (Daimon)
This paper describes the characteristics of criteria, thus clarifying Wittgenstein´s criteriological view, his view of the mental, and why he is not a behaviorist. We find that criterion for is a two-place, irreflexive, nonsymmetrical relation. There are often many different criteria for the same state of affairs. Under normal circumstances, a criterion for something provides us with evidence for that something´s being the case. However, a criterion for something is usually neither a necessary nor a sufficient condition for it; hence satisfying a criterion does not in general provide us with logically decisive evidence that the thing in question obtains. Criteria can be distinguished from mere evidence as follows: X is a criterion for Y only if learning the full meaning of Y requires that we grasp the connection between X and Y; they are tied together conceptually. That X is mere evidence for Y, in contrast, implies that we can learn the full meaning of Y without grasping the connection between X and Y. Finally, criteria for mental or psychological events are not always directly observable, and psychological concepts are not always employed on the basis of their criteria. Of psychological verbs, for instance, this asymmetry between the first-person singular and the second - and third-person use in the present tense is characteristic of the mental.